70% off : the investor's guide to discount brokerage - Coler, Mark D.; Ratner, Ellis M. (New York : Facts on File, 1983)
This book discusses the different types of brokerage and their characteristics.
Includes index.
osc 28/3/18
Loans
Keywords: Discount brokers